Linking Belief to Thought: A Structural Equation Modeling Analysis of Self-Efficacy and Critical Thinking Among Indonesian Pre-Service Teacher - Lia Angela; Rhomiy Handican; Anriany Casanova (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
This study aims to examine the relationship between self-efficacy and critical thinking skills among pre-service teachers in Indonesia. It seeks to provide empirical insights into how beliefs in one's own capabilities influence the propensity for critical thinking within the context of teacher education. A correlational quantitative design was employed, involving 426 pre-service teachers from eight universities across six provinces. Data were collected using the California Critical Thinking Tendency Scale and the Teacher Self-Efficacy Scale, and analyzed through Structural Equation Modeling (SEM). The results revealed a significant direct effect of self-efficacy on critical thinking skills, with a coefficient of 0.44. Indirect effects were also observed on sub-factors such as analytical thinking (0.35), open-mindedness (0.35), inquisitiveness (0.33), confidence in reasoning (0.33), truth-seeking (0.33), and systematicity (0.28). Model fit indices—including RMSEA (0.061), CFI (0.98), and TLI (0.97)—indicated a good fit, confirming the model’s validity. These findings underscore the importance of strengthening self-efficacy in teacher education programs as a strategic pathway to enhance critical thinking skills among future educators. Furthermore, the study contributes empirical evidence to inform the design of teacher education curricula that prioritize both personal and professional development.